Three months-old’ preferences for biological motion configuration and its subsequent decline - Lisboa, Maria Isabel Almeida Costa Pinto (2022)
To perceive, identify and understand the action of others, it is essential to perceptually organize individual and local moving body parts (such as limbs) into the whole configuration of a human body in action. Configural processing—processing the relations among features or parts of a stimulus—is a fundamental ability in the perception of several important social stimuli, such as faces or biological motion. Despite this, we know very little about how human infants develop the ability to perceive and prefer configural relations in biological motion. We present two preferential looking experiments (one cross-sectional and one longitudinal) measuring infants’ preferential attention between a coherent motion configuration of a person walking vs. a scrambled point-light walker (i.e., a stimulus in which all configural relations were removed, thus, in which the perception of a person is impossible). We found that three-month-old infants prefer a coherent point-light walker in relation to a scrambled display, but both five- and seven-month-old infants do not show any preference. We discuss our findings in terms of the different perceptual, attentional, motor, and brain processes available at each age group, and how they dynamically interact with selective attention toward the coherent and socially relevant motion of a person walking during our first year of life.